Physical activity promotion: A cross-sectional study exploring the practice, attitudes, and barriers amongst Luxembourg’s healthcare professionals - Bahdur, Khatija; Martins, Miguel; Carson, Fraser (Health Promotion & Physical Activity, 2024)
Purpose: Physical activity (PA) is known to help prevent and minimise the impact of Non-Communicable Diseases (NCDs). This study aimed to explore the attitudes and practices of general practitioners (GPs) and physiotherapists (PTs) in Luxembourg towards promoting PA and the barriers they face. Material and methods: A total of 174 healthcare professionals (100 GPs and 74 PTs) completed an anonymous electronic questionnaire, which included questions on demographics, attitudes towards PA prescription, the importance of PA as a preventative and treatment modality for NCDs, barriers to exercise prescription, and interest in expanding their knowledge about PA. Results: The results revealed that 56% of HCPs recommended PA weekly, with 43.7% providing detailed guidelines. Most HCPs (71.6%) acknowledged the importance of PA for managing and preventing chronic conditions. The main barriers to PA counselling were lack of time (23.6%), lack of knowledge (10.9%), and patients preferring medication over exercise (30.5%). Conclusions: While the study found that healthcare professionals in Luxembourg have positive attitudes towards PA, there are still limitations in prescribing and recommending PA.